(untitled) (International Journal of Banking and Finance, 2009)
Eastern European countries, which are candidates for accord into the Exchange Rate Mechanism (ERM) and the eventual move towards Euro, fi nd exchange rate management a tedious challenge. This paper examines the underlying factors that move exchange rates and helps us to contribute towards streamlining policies and strategies in moving these countries forward. The new findings on exchange rate determinants for this group of transitional economies are based on parity factors as well as non-parity factor effects. The evidence that emerges from this paper is that non-parity factors including economic growth rate, current account and capital flows are significantly correlated with exchange rates. The results are robust whichever data set is used, high-frequency and low-frequency data sets.